2015
DOI: 10.1007/s10096-015-2385-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibody responses against Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis proteins in children with community-acquired pneumonia: effects of combining pneumococcal antigens, pre-existing antibody levels, sampling interval, age, and duration of illness

Abstract: We evaluated the effects of combining different numbers of pneumococcal antigens, pre-existing antibody levels, sampling interval, age, and duration of illness on the detection of IgG responses against eight Streptococcus pneumoniae proteins, three Haemophilus influenzae proteins, and five Moraxella catarrhalis proteins in 690 children aged <5 years with pneumonia. Serological tests were performed on acute and convalescent serum samples with a multiplexed bead-based immunoassay. The median sampling interval wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
10
1
1
Order By: Relevance
“…The included unvaccinated children had similar demographic and serological characteristics when compared with the PNEUMOPAC cohort, whose data have been previously published. 19 The comparison of the baseline clinical features for vaccinated and unvaccinated children demonstrated no significant difference between the study subgroups, as shown in Table 1.…”
Section: Study Groupmentioning
confidence: 97%
“…The included unvaccinated children had similar demographic and serological characteristics when compared with the PNEUMOPAC cohort, whose data have been previously published. 19 The comparison of the baseline clinical features for vaccinated and unvaccinated children demonstrated no significant difference between the study subgroups, as shown in Table 1.…”
Section: Study Groupmentioning
confidence: 97%
“…20 Infecções bacterianas típicas também foram pesquisadas, com a quantificação de títulos específicos de IgG: de 690 pacientes com amostras de soro pareadas disponíveis para esses ensaios, a taxa de respostas de anticorpos foi de 15,4% para pelo menos um antígeno da proteína pneumocócica, 5,8% para H. influenzae e 2,3% para M. catarrhalis, a taxa de detecção de anticorpos foi significativamente aumentada para pelo menos uma dessas três bactérias para 20,4%. 21 Foram também investigadas infecções bacterianas atípicas: a infecção aguda por M. pneumoniae foi diagnosticada pela detecção de anticorpos IgM específicos na amostra de soro convalescente, infecções agudas por Chlamydia pneumoniae e Chlamydia trachomatis foram diagnosticadas pela detecção de anticorpos IgM específicos ou mudanças significativas nos títulos de IgG ou IgA; foram diagnosticadas infecções agudas por M. pneumoniae (86/787; 10,9%), C. pneumoniae (79/733; 10,8%) e C. trachomatis (3/28; 10,7%) e 147 (20,1%), 731 pacientes investigados para essas três bactérias tinham infecção aguda por pelo menos uma dessas três bactérias (18 pacientes tinham testes concomitantemente positivos para infecção aguda por M. pneumoniae e C. pneumoniae). 22 Com base nos dados supracitados, é possível observar que os vírus respiratórios têm sido cada vez mais implicados na etiologia da PAC na infância, juntamente com o reconhecimento de que as infecções virais foram mais frequentes do que as bacterianas, mesmo em países em desenvolvimento.…”
Section: Etiologiaunclassified
“…Furthermore, Jiménez-Munguía et al also described that the levels of specific IgG against PcpA were three times lower in sera of children with pneumonia collected up to 10 days of disease, when compared to that of negative controls (Jiménez-Munguía et al, 2015). Similar results were found for the evaluation of antibody responses in a cohort of 690 children with non-severe community-acquired pneumonia, in which PcpA and PcsB were the antigens with the highest rate of antibody response detection (Borges et al, 2015).…”
Section: Tablementioning
confidence: 61%
“…Invasive pneumococcal pneumonia was diagnosed by the isolation of S. pneumoniae on blood culture (9 patients) or by the detection of pneumococcal DNA in the buffy-coat (4 patients) using PCR with the ply primers. Data about this study group have been previously published elsewhere (Nascimento-Carvalho et al, 2008;Borges et al, 2015).…”
Section: Positive Controlsmentioning
confidence: 99%